Effect of topspin on the apparent speed of a tennis court - Cross, R. (Sports Engineering, 2019)
Experimental results are presented concerning the impact of a tennis ball incident obliquely with topspin on a rigid, horizontal surface. The ball was launched at speeds between 12 and 17 m/s onto P800 emery paper attached to a heavy block of granite. The angle of incidence to the surface was varied from 14° to 65° and the spin of the ball was varied from 0 to 360 rad/s to examine the effects on the horizontal rebound speed. The ratio of the rebound to the incident horizontal speed increased from 0.5 to 0.95 as the incident spin was increased. The classification or perception of a tennis court as being fast or slow is therefore of limited value, given that most players strike the ball with topspin.